Heyzine Flipbook as a Learning Media: Development of a Digital Realistic Mathematics Education Module - Amany, Azzah; Murtiyasa, Budi; Masduki (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
The high level of difficulty students face in mastering the concept of congruence, coupled with teachers' pedagogical constraints in presenting the material contextually, underlies the main objective of this research. This development research aims to produce and test an interactive digital module based on Realistic Mathematics Education (RME) as an effort to improve students' conceptual understanding of congruence material. The research method adopted the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) with data collection using expert validation, student response questionnaires, and analysis of pretest-posttest results. The findings show that the developed module achieves high validity, practicality, and effectiveness criteria for use in mathematics learning. These results confirm that the integration of an interactive digital module based on RME is a significant solution in bridging the abstraction of mathematical concepts, while simultaneously advancing innovative and effective digital learning practices. Abstrak Tingginya kesulitan siswa dalam menguasai konsep kekongruenan, yang diiringi oleh kendala pedagogis guru dalam menyajikan materi secara kontekstual, melatarbelakangi tujuan utama penelitian ini. Penelitian pengembangan ini bertujuan menghasilkan dan menguji modul digital interaktif berbasis Realistic Mathematics Education (RME) sebagai Upaya untuk meningkatkan pemahaman konseptual siswa pada materi kekongruenan. Metode penelitian mengadopsi model ADDIE (Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi) dengan pengumpulan data menggunakan validasi ahli, kuesioner respon siswa, dan analisis hasil pretest-posttest. Temuan menunjukkan bahwa modul yang dikembangkan mencapai kriteria validitas, kepraktisan, dan efektivitas yang tinggi untuk digunakan dalam pembelajaran matematika. Hasil ini menegaskan bahwa integrasi modul digital interaktif berbasis RME merupakan solusi yang signifikan dalam menjembatani abstraksi konsep matematika, sekaligus memajukan praktik pembelajaran digital yang inovatif dan efektif.